2012
DOI: 10.1603/me11150
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Correlation Map Analyses Show Weather Variation Influences on Mosquito Abundance Patterns in Saginaw County, Michigan, 1989–2005

Abstract: Weather is important determinant of mosquito abundance that, in turn, influences vectorborne disease dynamics. In temperate regions, transmission generally is seasonal as mosquito abundance and behavior varies with temperature, precipitation, and other meteorological factors. We investigated how such factors affected species-specific mosquito abundance patterns in Saginaw County, MI, during a 17-yr period. Systematic sampling was undertaken at 22 trapping sites from May to September, during 1989-2005, for 19,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…Mosquito capture rates increased with increasing temperature, as already shown in previous studies [5,6]. Furthermore, it has been demonstrated that considerable changes in the temperature at the capture event compared to the previous days affect the number of captured mosquitoes.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Mosquito capture rates increased with increasing temperature, as already shown in previous studies [5,6]. Furthermore, it has been demonstrated that considerable changes in the temperature at the capture event compared to the previous days affect the number of captured mosquitoes.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have already confirmed that population densities vary strongly with temperature [5,6]. This is due to the temperature dependence of the development rates of eggs, larvae and pupae, survival rates of immatures as well as imagos.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, the temporal variations can probably be traced back to usage patterns. The insect repellent DEET is widely used not only in households but also with outdoor recreational activities and its usage may increase as a result of higher abundance of mosquitoes during the monsoons and high humidity periods (Chuang et al, 2012), leading to the relatively higher loads. We assign the variation of caffeine concentrations in the reservoir to rainfall, but other frequently detected wastewater indicators, such as salicylic acid and crotamiton, showed no dependence with cumulative precipitation.…”
Section: Temporal Variationmentioning
confidence: 99%